Encyclopedia of database technologies and applications - Rivero, Laura C., 1956-; Doorn, Jorge H., 1946-; Ferraggine, Viviana, 1961- (Hershey, PA : Idea Group Reference, 2006)
'This encyclopedia will be a collection of diverse topics related to databases, providing an overview not only of the state of the art of classical subjects but also clear and concise explanations of the latest technology, its practical applications and research directions'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Database management -- Encyclopedias